ANALISIS RANCANGAN TEKNOLOGI MOBILE APPLICATION PADA E-BOOKING RUANGAN UNTUK KEGIATAN UKM - Purwanto, Agus; Nugroho, Anggun (Jurnal Teknologi Informasi dan Komputer, 2018)
ABSTRACT Students Activity Unit or abbreviated UKM in STIKOM Bali is a student organization managed by students under the coordination of Assistant III Chairman of Student Affairs. Activities undertaken by SMEs is a non-academic activities that are useful to mediate interests and talents of students in the field of non-academic. Currently more than 25 SMEs in STIKOM Bali are coordinated by PK III. Activities undertaken are usually done on campus and off campus by utilizing the space and fascities available on campus itself. To use the existing room and facilities SME managers must place orders to the relevant sections so that their use can be controlled. Room reservation system is done so far still using the manual way that SME managers come directly to units of Facilities and Infrastructure (SARPRAS) to reserve the space to be used. Therefore, it is necessary to apply for room rental booking with Android based for SME managers easier to book the room. but also to facilitate SME managers to obtain information on the available space at the desired time. With the application of this application later lending space can be resolved by using information and communication technology (ICT), without having to come directly to the unit Sarpras so that the relevant part easier to manage and monitor the use of the room by SMEs in STIKOM Bali. This mobile app is built using android operating system using Android Studio. This application allows customers to register and make room reservations in accordance with the time required and the type of room in accordance with the capacity of the room. This application also uses My SQL for database storage as well as using the application adobe dreamweaver to create a web server to be easily dikelaola by the administrator in this Sarpras unit. Keywords : ukm, booking, booking system, android ABSTRAK Unit Kegiatan Mahaiswa atau disingkat UKM di STIKOM Bali merupakan organisasi mahasiswa yang dikelola oleh mahasiswa dibawah koordinasi Pembantu Ketua III Bidang Kemahasiswaan. Kegiatan yang dilakukan oleh UKM ini adalah kegiatan non akademis yang berguna untuk memediasi minat dan bakat para mahasiswa di bidang non akademis. Saat ini lebih dari 25 UKM di STIKOM Bali yang dikoordinasi oleh PK III. Kegiatan-kegiatan yang dilakukan biasanya dilakukan di kampus dan di luar kampus dengan memanfaatkan ruangn dan fasislitas yang tersedia di kampus itu sendiri. Untuk menggunakan ruangan dan fasilitas yang ada para pengurus UKM harus melakukan pemesanan ke bagian terkait agar penggunaannya dapat terkontrol. Sistem pemesanan ruangan yang dilakukan selama ini masih menggunakan cara manual yaitu pengurus UKM datang langsung ke unit Sarana dan Prasarana (SARPRAS) untuk memesan ruang yang akan digunakan. Oleh karena itu, diperlukan aplikasi pemesanan peminjaman ruangan dengan berbasis Android agar pengurus UKM lebih mudah untuk memesan ruangan. selain itu juga untuk memudahkan pengurus UKM memperoleh informasi ruangan yang tersedia pada waktu yang diinginkan. Aplikasi mobile ini dibangun dengan menggunakan sistem operasi android dengan menggunakan Android Studio. Aplikasi ini memungkinkan pelanggan melakukan registrasi dan melakukan pemesanan ruangan sesuai dengan waktu yang dibutuhkan serta jenis ruangan sesuai dengan kapasitas ruangan. Aplikasi ini juga menggunakan My SQL untuk penyimpanan basis data serta menggunakan aplikasi adobe dreamweaver untuk membuat web server agar dapat mudah dikelaola oleh administrator dalam hal ini unit Sarpras. Kata kunci : ukm,pemesanan, sistem booking, android